Une histoire de l’oeil - Paré, André-Louis (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
AbstractThe author bases himself on Michel Foucault's analysis of Jeremy Bentham's Panopticon to examine the works of Emmanuelle Léonard — more specifically, the video installation Guardia, resguárdeme (Guard, protect me), made in 2005. In Mexico City, Léonard followed security guards wearing a hat in which she had hidden a surveillance camera. Based on disciplinary subjection of bodies, our societies and democracies have become panoptic and subscribe to a policy of visibility transformed into the policing of behaviours. In confronting this policy, Léonard devises tactics and strategies of resistance to the panopticism of urban life. In opposition to Guy Debord, who criticizes society starting from the notion of spectacle, there may be reason to think, with Foucault, that the urban space is more propitious to generalized surveillance.